Variable Clinical Presentations of Riedel's Thyroiditis: Report of Two Cases. (8th August 2011) - Zakeri, Hamidreza; Kashi, Zahra
Abstract : Riedel's thyroiditis is a rare inflammatory disease of the thyroid gland and has been reported in 0.05% of thyroid surgeries. Herein we report two cases of Riedel's thyroiditis with variable clinical presentations. One of these cases was a 51-year-old man who was presented with hypothyroidism and the other a 17-year-old young male with thyrotoxicosis. In these cases, age may be a determining factor in presenting symptoms and signs, disease process, and response to treatment.